2010
DOI: 10.1177/0042085910377297
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Trust Building Between University Researchers and Urban School Personnel

Abstract: A wide range of research has examined trust building within corporations, businesses, and schools, and between and within organizations, but little research has been conducted that examines trust formation between university researchers and classroom-based teachers. Using a qualitative methodological approach, the authors examined the development of trusting relationships between their educational research team and a series of urban science teachers after 3 years of partnerships. It was found that teachers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 32 publications
3
14
0
17
Order By: Relevance
“…The two antecedents that all stakeholder groups rated as relatively most important (i.e., "authentic, effective, and transparent communication" and "mutually respectful and reciprocal relationships") both relate to colearning processes involving transactions between parties in terms of information, experiences, or services. Qualitative research has found that effective communication and positive interpersonal interactions are important facilitators of trust and successful community-academic research partnerships (Barnett, Anderson, Houle, Higginbotham, & Gatling, 2010;White-Cooper, Dawkins, Kamin, & Anderson, 2009). Our study strengthens empirical evidence that communication and relationships are perceived as most important to trust across stakeholder groups, and indicates the importance of co-learning within research.…”
Section: Discussionsupporting
confidence: 78%
“…The two antecedents that all stakeholder groups rated as relatively most important (i.e., "authentic, effective, and transparent communication" and "mutually respectful and reciprocal relationships") both relate to colearning processes involving transactions between parties in terms of information, experiences, or services. Qualitative research has found that effective communication and positive interpersonal interactions are important facilitators of trust and successful community-academic research partnerships (Barnett, Anderson, Houle, Higginbotham, & Gatling, 2010;White-Cooper, Dawkins, Kamin, & Anderson, 2009). Our study strengthens empirical evidence that communication and relationships are perceived as most important to trust across stakeholder groups, and indicates the importance of co-learning within research.…”
Section: Discussionsupporting
confidence: 78%
“…supports both the findings of Barnett et al (2010) on the process of trust building between teachers and researchers, and Skinner et al (2014) on the dilemma that can occur in trust building.…”
Section: Illustrative Case Studysupporting
confidence: 67%
“…Whereas other researchers have reported on the nature of trust, the process of trust building, and the importance of trust in management, the process by which individuals engage in trust building has received less attention (Barnett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, opportunistic policies at some of the colleges kept high school partners from seeing those institutions as operating in good faith. As numerous other studies have shown, effective implementation of new programs depends on the alignment of aims and resources (e.g., Cohen & Spillane, 1992;Spillane, Diamond, Walker, Halverson, & Jita, 2001) as well as on conditions productive of mutual trust between partners (e.g., M. Barnett, Anderson, Houle, Higginbotham, & Gatling, 2010;Dhillon, 2009). Furthermore, as our findings suggest, dual enrollment and early college options can provide efficiencies in poor and rural regions so long as the arrangements are positioned as a synergy (i.e., an alignment of resources) and not as a competition for resources.…”
Section: Discussionmentioning
confidence: 99%